Conservation priorities in Central Asia: the Shorsuv Massif IPA and its role in the Fergana Valley’s biodiversity - Komiljon Sh. Tojibaev; Hushbaht R. Hoshimov; Rustam R. Gulomov; Obidjon Kh. Sheraliev; Farkhod I. Karimov; Laura Kor; Avazbek R. Batoshov; Shukherdorj Baasanmunkh; Ju Eun Jang; Joonhyung Jung; Hee-Young Gil; Hyeok Jae Choi (Frontiers in Conservation Science, 2025)
IntroductionThe Fergana Valley (FV), a hotspot of endemicity and one of the most densely populated regions in Central Asia, faces increasing anthropogenic pressure.MethodsIn this study, geospatial conservation assessment and grid-based mapping of wild flora were integrated with traditional IPA identification methods recommended by Plantlife, resulting in a significant enhancement of the standard IPA approach.ResultsThe Shorsuv Massif and its surrounding areas were identified as an IPA, meeting Criteria A and C of the IPA criterion developed by Plantlife. Given the unique biodiversity of the FV, the lack of IUCN Category I protected areas in the Uzbek part, and the increasing pressure of human activities, documentation and conservation of the plant diversity according to Plantlife criteria is of global importance. As a continuation of research in this direction, this paper details the identification of a third IPA in FV, located in the variegated outcrops of the Turkestan Range in the southwest of FV. Detailed field surveys and grid mapping documented 349 vascular plant species, including 42 threatened species under Criterion A of Plantlife International. However, the site and its surroundings are critically threatened by large-scale mining activities (Criterion C).ConclusionsThe first results of this study and their discussion with authorized representatives provides crucial data for informing the government’s decision to establish a new protected area in the FV. According to Decree No. PP-171 of the President of the Republic of Uzbekistan, dated 31 May 2023, a national park will be created, encompassing 100,000 hectares, including the Shorsuv IPA site and adjacent areas. This initiative also supports global conservation targets outlined in the Kunming-Montreal Global Biodiversity Framework (GBF) and the Global Strategy for Plant Conservation (GSPC).